A generation apart? Youth and political participation in Britain - Henn, Matt; Wring, Dominic; Weinstein, Mark (2002)
Conventional wisdom holds that young people in Britain are alienated from politics, with some claiming that this reflects a wider crisis of legitimacy that should be met by initiatives to increase citizenship. this article addresses these areas, presenting both panel survey and focus group data from first-time voters. It concludes that, contrary to the finds from many predominantly quantitative studies of political participation, young people are interested in political matters, and do support the democratic process. However, they feel a sense of anti-climax having voted for the first time, and are critical of those who have been elected to positions of political power. If they are a generation apart, this is less to do with apathy, and more to do with their engaged specticism about `formal' politics in Britain. - Reproduced.
Keywords: Youth participation - Great Britain; Youth participation